Long-Term Clinical Performance of Zirconia-Based Prostheses in Posterior Teeth Rehabilitation - Laziz ugli, Abdukhamidov Jurabek; Astanovich, Akhmedov Alisher (American Journal of Bioscience and Clinical Integrity, 2026)
The use of zirconia-based prostheses for posterior teeth rehabilitation has gained widespread acceptance due to their favorable mechanical properties, esthetic potential, and biocompatibility. This study evaluates the long-term clinical performance of zirconia restorations in posterior regions, focusing on survival rate, marginal integrity, chipping incidence, wear patterns, and periodontal health. Evidence from longitudinal clinical trials and systematic reviews indicates that monolithic and veneered zirconia crowns and bridges demonstrate high survival rates, low complication frequencies, and predictable functional outcomes over periods exceeding five years. Factors influencing performance include material composition, sintering protocols, prosthesis design, occlusal scheme, antagonist material, and cementation technique. Clinical outcomes are assessed in terms of structural stability, occlusal adaptation, patient-reported satisfaction, and biological response of supporting periodontal tissues. Findings support the use of zirconia prostheses as a reliable restorative option for posterior dentition, combining durability, esthetics, and periodontal compatibility. The study underscores the importance of meticulous preparation, appropriate occlusal adjustment, and adherence to manufacturer guidelines to optimize long-term success.